Autism and sleep disorders. - Devnani, Preeti A.; Hegde, Anaita U. (Journal of Pediatric Neurosciences)
Autism Spectrum Disorders” (ASDs) are neurodevelopment disorders and are characterized by persistent impairments in reciprocal social interaction and communication. Sleep problems in ASD, are a prominent feature that have an impact on social interaction, day to day life, academic achievement, and have been correlated with increased maternal stress and parental sleep disruption. Polysomnography studies of ASD children showed most of their abnormalities related to rapid eye movement (REM) sleep which included decreased quantity, increased undifferentiated sleep, immature organization of eye movements into discrete bursts, decreased time in bed, total sleep time, REM sleep latency, and increased proportion of stage 1 sleep. Implementation of nonpharmacotherapeutic measures such as bedtime routines and sleep‑wise approach is the mainstay of behavioral management. Treatment strategies along with limited regulated pharmacotherapy can help improve the quality of life in ASD children and have a beneficial impact on the family. PubMed search was performed for English language articles from January 1995 to January 2015. Following key words: Autism spectrum disorder, sleep disorders and autism, REM sleep and autism, cognitive behavioral therapy, sleep‑wise approach, melatonin and ASD were used. Only articles reporting primary data relevant to the above questions were included.